Nurses’ job satisfaction assessment by areas of care - Silva, Cláudia Isabel Neves Pacheco da; Potra, Teresa Maria Ferreira dos Santos (Revista da Escola de Enfermagem da USP, 2021)
Objective: To analyze the level of nurses’ job satisfaction according to the area of care provided in a Local Health Unit, in Portugal. Method: This is a quantitative, descriptive, analytical study, with observational and cross-sectional design. The Job Satisfaction Assessment Instrument was used for data collection. Results: Sample (n = 218), predominantly female (84.6%), with a mean age of 33 years. The area of care delivery influences total job satisfaction (p < 0.05) and some of the dimensions studied (p < 0.05). Nurses from Community Care Units show greater job satisfaction, followed by nurses from Indirect Care. Critical Care nurses show lower job satisfaction, followed by those who work in outpatient’s units. Most nurses show lower satisfaction level in the aspect Management Bodies and in the dimension Quality of Care Delivery. Conclusion The most satisfied nurses are those from the Community Care Units and the nurses with the lowest level of job satisfaction are those from Critical Care.